2001
DOI: 10.1128/iai.69.4.2739-2742.2001
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi Proteins Whose Expression Is Similarly Affected by Culture Temperature and pH

Abstract: Previously, we had demonstrated the upregulation in the expression of several proteins, including the lipoproteins OspC and P35, of Borrelia burgdorferi in the stationary growth phase. Since the expression of OspC is also known to be affected by culture temperature and pH, we examined the effects of both variables on the expression of the remaining stationary-phase-upregulated proteins. Our study revealed that the expression of each of the remaining stationary-phase-upregulated proteins, P35 included, was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 26 publications
2
55
1
1
Order By: Relevance
“…The ability of the organism to switch on a common regulatory network suggest that there is a class of 'stress regulated' genes that are regulated by common sensing mechanism in response to different environmental signals [6,35]. The results of the present study indicating the overlapping expression of proteins under different stress conditions are in agreement with earlier studies of Chander et al [21] and Ramamoorthy and Schoel-Meeker [36]. The results suggest that expression of proteins does not depend on single environmental stimulus in host but there may be an interaction among stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of the organism to switch on a common regulatory network suggest that there is a class of 'stress regulated' genes that are regulated by common sensing mechanism in response to different environmental signals [6,35]. The results of the present study indicating the overlapping expression of proteins under different stress conditions are in agreement with earlier studies of Chander et al [21] and Ramamoorthy and Schoel-Meeker [36]. The results suggest that expression of proteins does not depend on single environmental stimulus in host but there may be an interaction among stimuli.…”
Section: Discussionsupporting
confidence: 92%
“…We and others have previously observed that some spirochete proteins involved in mammalian infection are regulated by temperature, with greater amounts of protein synthesized by bacteria cultivated at temperatures similar to the mammalian body temperature than by bacteria grown at ambient temperature (17,31,38,46,51,54,55,62). For these reasons, we examined the levels of RevA protein synthesized by bacteria cultivated at either 23 or 34°C.…”
Section: Resultsmentioning
confidence: 99%
“…Since the production of some B. burgdorferi proteins preferentially synthesized during infection of warm-blooded animals are also regulated by pH (12,13,46,62), we examined the effect of culture medium pH on RevA expression. Significantly higher levels of RevA were produced by bacteria cultivated in medium buffered to remain at pH 7.0 than by those grown in medium having a pH of 8.0 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that the vlsE locus falls into the growing category of Borrelia genes that are preferentially expressed in the host and not the vector (10,13). Several studies have identified temperature and pH as signals that regulate the expression of Borrelia genes (7,8,28,35,39). These signals are likely to play a role during natural transmission, because spirochetes experience an increase in temperature and decrease in pH as they move from the vector to the vertebrate.…”
Section: Discussionmentioning
confidence: 99%